Effect of pretreatment with Mycobacterium bovis (strain BCG) and immune syphilitic serum on rabbit resistance to Treponema pallidum. - Graves, S R (1975)
Stimulation of the rabbit reticuloendothelial system with viable Mycobacterium bovis (strain BCG), and other agents, had no effect on the development of syphilitic lesions after intradermal or intravenous inoculation with graded doses of Treponema pallidum (virulent Nichol's strain; mean infective doses less than 10). The simultaneous administration of immune syphilitic rabbit serum retarded the development of lesions, but this appeared to be due solely to the immune serum, suggesting no synergism between the activated reticuloendothelial system and the anti-T. pallidum antibodies. The administration of two doses of BCG enhanced syphilitic lesion development in the rabbit.